Digestible valine requirements for broilers from 22 and 42 days old - Duarte, Karina Ferreira [UNESP]; Junqueira, Otto Mack [UNESP]; Domingues, Carla Heloísa De Faria [UNESP]; Filardi, Rosemeire Da Silva [UNESP]; Borges, Liliana Longo [UNESP]; Praes, Maria Fernanda Ferreira Menegucci [UNESP] (Editora da Universidade Estadual de Maringá (EDUEM), 2014)
Current experiment established different criteria to evaluate the requirements of digestible valine for broilers from 22 and 42 days of age, by different regression models (quadratic, exponential and Linear Response Plateau) and, in the case of statistical significance, the comparison of means by Duncan test at 5% probability. A total of 1,920 Cobb 500 male broilers were used and distributed in an entirely randomized experimental design, with 6 treatments (6 digestible valine levels: 0.7192, 0.7729, 0.8265, 0.8802, 0.9339 and 0.9876%) and 8 replications, with 40 broilers each. Data on performance and carcass characteristics were evaluated. The level of 0.8265% digestible valine was considered standard. The inclusion of 0.816, 0.848 and 0.903% of digestible valine levels, corresponding to digestible valine:lysine ratios of approximately 76.00%, 79.00% and 84.12%, provided best feed intake, weight gain and feed conversion ratio, respectively for broiler from 22 to 42 days of age.

Um experimento foi realizado com o objetivo de estabelecer critérios de avaliação das exigências de valina digestível para frangos de corte de 22 a 42 dias de idade utilizando-se diferentes modelos de regressão (quadrático, exponencial e de retas segmentadas ou Linear Response Plateau). Foram utilizados 1.920 frangos de corte machos com 22 dias de idade, distribuídos em delineamento inteiramente ao acaso, com seis tratamentos (6 níveis de valina digestível: 0,7192; 0,7729; 0,8265; 0,8802; 0,9339 e 0,9876) e oito repetições de 40 aves. Utilizou-se como padrão o nível de 0,8265% de valina digestível. A inclusão dos níveis 0,8160; 0,8484 e 0,9031% de valina digestível proporcionou os melhores resultados de consumo de ração, ganho de peso e conversão alimentar respectivamente.
Exigências em valina digestível para frangos de corte de 22 a 42 dias de idade
Keywords: Digestible amino acid; Ideal protein; Performance; Regression analysis; Aminoácidos digestíveis; Proteína ideal; Desempenho; Análise de regressão